Patogenômica de Corynebacterium silvaticum - Marcus Vinicius Canário Viana (2022)
Corynebacterium silvaticum is a recently described pathogenic gram-positive bacterium belonging to the C. diphtheriae group, a group of species have the potential to produce diphtheria toxin (DT). The species was described in 2020 as not producing diphtheria toxin and capable of infecting wild pigs and deer, causing disease similar to caseous lymphadenitis caused by C. pseudotuberculosis biovar ovis in goats and sheep. The first samples were isolated in Germany and Austria. In 2014, the species was isolated for the first time from domestic pigs and, in Portugal, it was misclassified as C. pseudotuberculosis. Little is known about its pathogenicity mechanisms beyond the phospholipase D virulence factor, two host species (pig and deer) or geographical distribution (Germany, Austria, Switzerland and Portugal). This work aimed to use genomic analyzes to investigate diversity, mechanisms of pathogenicity, develop molecular markers for diagnosis by PCR and proteins under positive selection. Compared to the closest species C. ulcerans, C. silvaticum is more homogeneous, with 75.2% of genes conserved, and has eight genomic islands. 18 of 36 virulence factors described in Corynebacterium are present in the core genome. The genomes form two clades, one of which is represented by lineages from Portugal and 05-13 from Austria that probably produce DT due to the absence of a frameshift of the tox gene. Marker genes were found for both clades and for samples from Portugal. No genes were identified as under positive selection. In summary, C. silvaticum is a clonal species and predicted to have the potential to cause zoonosis and diphtheria in humans, but DT production must be experimentally verified in the strains from Portugal and 05-13.